Diagnostic performance of cardiac magnetic resonance segmental myocardial strain for detecting microvascular obstruction and late gadolinium enhancement in patients presenting after a ST-elevation myocardial infarction - Gräni, Christoph; Stark, Anselm W.; Fischer, Kady; Fürholz, Monika; Wahl, Andreas; Erne, Sophie A.; Huber, Adrian T.; Guensch, Dominik P.; Vollenbroich, René; Ruberti, Andrea; Dobner, Stephan; Heg, Dik; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Microvascular obstruction (MVO) and Late Gadolinium Enhancement (LGE) assessed in cardiac magnetic resonance (CMR) are associated with adverse outcome in patients with ST-elevation myocardial infarction (STEMI). Our aim was to analyse the diagnostic performance of segmental strain for the detection of MVO and LGE. Methods: Patients with anterior STEMI, who underwent additional CMR were enrolled in this sub-study of the CARE-AMI trial. Using CMR feature tracking (FT) segmental circumferential peak strain (SCS) was measured and the diagnostic performance of SCS to discriminate MVO and LGE was assessed in a derivation and validation cohort. Results: Forty-eight STEMI patients (62±12 years old), 39 (81%) males, who underwent CMR (i.e. mean 3.0±1.5 days) after primary percutaneous coronary intervention (PCI) were included. All patients presented with LGE and in 40 (83%) patients, MVO was additionally present. Segments in all patients were visually classified and 146 (19%) segments showed MVO (i.e. LGE+/MVO+), 308 (40%) segments showed LGE and no MVO (i.e.LGE+/MVO-), and 314 (41%) segments showed no LGE (i.e.LGE-). Diagnostic performance of SCS for detecting MVO segments (i.e.LGE+/MVO+ versus LGE+/MVO- & LGE-) showed an AUC=0.764 and for LGE segments (i.e.LGE+/MVO+ & LGE+/MVO- versus LGE-) AUC=0.848. SCS cut-off value was -11.2%,resulting in a sensitivity of 78% and a specificity of 67% with a positive predictive value (PPV) of 94% and a negative predictive value (NPV) of 30% when tested in the validation group. For LGE+ segments, SCS with a cut-off value of -13.8% yielded to a sensitivity of 76%, specificity of 74%, PPV of 70% and NPV of 81%. Conclusion: Segmental strain in STEMI patients was associated with good diagnostic performance for detection of MVO+ segments and very good diagnostic performance of LGE+ segments. Segmental strain may be useful as a potential contrast-free surrogate marker to improve early risk stratification in patients after primary PCI.